Search for resonant pair production of Higgs bosons in the bbZZ channel in proton-proton collisions at √s=13 TeV; Physical Review D; Vol. 102, iss. 3 - Sirunyan A. M.; Tumasyan A. R.; Adam W. Wolfgang; Ambrogi F. Federico; Zhokin A. E. Aleksandr Sergeevich; Bergauer T. Thomas; Babaev A. A. Anton Anatoljevich; Okhotnikov V. V. Vitaly Vladimirovich (2019, 2019)
Title screen